Kun-mkhyen Kloṅ-[chen]-rab-ʼbyams kyi gsuṅ sñiṅ gram sum cu pa bźugs so = Thirty pieces of advice from the heart - Kloṅ-chen-pa Dri-med-ʼod-zer, 1308-1363 (Ogyan Kunsang Choekhorling, 1979)
Instructions on the essentials of Mahayana Buddhism; in didactic verse, according to the Nyingmapa tradition.